Electric Conductivity and Resistance of Mouse Oocyte Membranes to Eﬀect of Pulsed Electric Field in Cryoprotectant Solutions - Smolyaninova, Yevgeniya I.; Shigimaga, Viktor O.; Kolesnikova, Alla O.; Popivnenko, Lyudmila I.; Todrin, Aleksandr F. (Problems of Cryobiology and Cryomedicine, 2019)
Using the method of pulsed conductometry, the values of electric conductivity of mouse oocytes in 1.0 M solutions of penetrating cryoprotectants have been first determined and the stability of their plasma membranes to the effect of pulsed electric field of increasing intensity has been investigated. For the oocytes, incubated in ethylene glycol (EG), 1,2-propanediol (1,2-PD), 2,3-butanediol (2,3-BD) and dimethyl sulfoxide (DMSO) solutions, the electric conductivity values were (23.6 ± 3.4), (21.3 ± 5.8) and (21.0 ± 2.3) and (23.6 ± 7.1) μS/cm respectively. The values of electric conductivity for mouse oocytes in acetamide (AC) and formamide (FA) solutions were (16.5 ± 6.1) and (16.9 ±± 10.7) μS/cm, respectively. Cryoprotectant solutions, belonging to alcohols (EG, 2,3-BD), as well as DMSO, were shown to have a stabilizing effect on the mouse oocyte plasma membranes under electric field action. The AC and FA solutions caused no stabilizing effect on mouse oocyte membranes, which was manifested in development of irreversible electric breakdown of plasma membranes with increasing electric field intensity. Probl Cryobiol Cryomed 2018; 28(4): 311-321